Morphological notes on the synanthropic psocid Psoquilla marginepunctata Hagen (first finding of the family Psoquillidae in ltaly) (Bollettino di zoologia agraria e bachicoltura, 2024)
Specimens of Psoquilla marginepunctata Hagen, 1865 (Psocoptera: Psoquillidae) were found in December 1994 in the railway station of Fidenza (province of Parma, Italy) on pallets bearing castor-oil plant seeds imported from Brazil. P. marginepunctata is a circumtropical species introduced into some temperate lands; in the Tropics it occurs primarily outdoors; in temperate countries in houses, warehouses and greenhouses. Taxonomical notes and drawings of the mouthparts, wings of the brachypterous form and terminalia of both sexes of this species are provided.
Keywords: Psoquillidae; Psoquilla marginepunctata; incidental introduction; Italy; taxonomy